IMPLEMENTATION OF E-LEARNING POLICY IN THE RECOVERY OF EDUCATION POST HYDROMETEOROLOGICAL DISASTER IN ACEH PROVINCE 2025 - Kezhia Febrin Nadia Krista; Aulia Jasmine Zalfania Azzahra; Indah Prabawati; Firre An Suprapto; Wilda (STMIK Indonesia Banda Aceh, 2026)
The hydrometeorological disaster that occurred in several places in Aceh at the end of 2025 caused a major impact on the continuity of the education sector , especially in terms of access , continuity of learning , and quality of infrastructure . Damage to school facilities and infrastructure and disruption to student mobility made education a public issue that requires fast , adaptive , and measurable policy intervention . As an innovative response , in 2026 a support program for 1.2 million e-learning PINs was launched , initiated by the Police Science College (STIK) of the Indonesian National Police Education and Training Institute (Lemdiklat Polri) in collaboration with the I Love My Country Indonesia (ILMCI) Group, with distribution support by the Aceh Regional Police and technical follow-up by the Aceh Education Office. This program is aimed at affected areas , especially in Aceh Singkil Regency and Lhokseumawe City , with a target of 362,617 students in 2,805 schools from elementary to high school levels . This study aims to evaluate the implementation of the e - learning PIN assistance policy that functions to support the recovery of the education sector after the disaster . The method used is a qualitative descriptive qualitative approach by conducting Literature review . The findings of this study indicate that this policy plays an important role in supporting the sustainability of learning and expanding access to digital education . However , its implementation still faces several challenges , such as a lack of adequate infrastructure , minimal preparation of the workforce , and less than optimal coordination between sectors . This finding is in line with the views on policy implementation explained by George C. Edward III, highlighting that communication , resources , attitudes , and bureaucratic organization play a crucial role in determining the success of a policy.